2015
DOI: 10.1007/s00423-015-1321-z
|View full text |Cite
|
Sign up to set email alerts
|

Emergency pancreatic surgery—demanding and dangerous

Abstract: Emergency pancreatic operations are infrequent and mainly performed due to duodenal perforation or bleeding; blunt abdominal trauma is rarely leading to emergency pancreas resections. They are associated with an increased morbidity and mortality and require a high level of surgical as well as interdisciplinary experience. Perioperative anesthesiological care and interventional radiological complication management are essential to improve outcome in this selective patient collective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Thus, collection of data about the presence/ absence of hepatitis viruses have been proposed to further explore the potential effect of such viruses on clinical, pathological and outcomes in patients with PD for periampullary malignancies starting from our previous research suggesting that there might be some influences of hepatitis viruses on clinical and pathological features particularly for patients with pancreatic cancer (54) as it was shown for hepatocellular carcinoma (55). Furthermore, the elective or emergency indication for PD was also pointed out because, although a PD in an emergency setting is feasible (56), it is widely accepted to be associated with very high mortality rates (around 34.7%) even in high-volume centers (57). In the present series, there was one postoperative death out of the 3 patients with emergency PD (mortality rate of 33.3%), but the cause of death was not related to pancreatic surgery complications.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, collection of data about the presence/ absence of hepatitis viruses have been proposed to further explore the potential effect of such viruses on clinical, pathological and outcomes in patients with PD for periampullary malignancies starting from our previous research suggesting that there might be some influences of hepatitis viruses on clinical and pathological features particularly for patients with pancreatic cancer (54) as it was shown for hepatocellular carcinoma (55). Furthermore, the elective or emergency indication for PD was also pointed out because, although a PD in an emergency setting is feasible (56), it is widely accepted to be associated with very high mortality rates (around 34.7%) even in high-volume centers (57). In the present series, there was one postoperative death out of the 3 patients with emergency PD (mortality rate of 33.3%), but the cause of death was not related to pancreatic surgery complications.…”
Section: Discussionmentioning
confidence: 98%
“…Reports of mortality following pancreatic injury have ranged from 12 to 35%. 9,28 The previously discussed review of the National Trauma Data Bank for pediatric blunt pancreatic trauma found a mortality of 2.5%, specifically for operatively managed patients, and 6.7% for nonoperatively managed patients. 24 Cause of death also did not differ significantly between the pediatric and adult populations, likely due to the overall low mortality rate in our data.…”
Section: Discussionmentioning
confidence: 99%
“…A surgical team familiar with HPB surgery can adapt to the emergency situation and also provide better postoperative care because it is customized with post-op complications and can treat them accordingly. Interdisciplinary communication and expertise can provide better outcomes (6,7).…”
Section: Discusionsmentioning
confidence: 99%
“…Prognosis depends on the timing to intervention, the experience of the operating surgeon, on the peri-and postoperative anesthesiological management and on the radiological management of postoperative complications (6,7).…”
Section: Discusionsmentioning
confidence: 99%